The Lower !Garib - Orange River - Lenggenhager, Luregn; Akawa, Martha; Miescher, Giorgio; Nghitevelekwa, Romie; Sinthumule, Ndidzulafhi Innocent (2023)
The Lower !Garib, or Orange River, flows through the historical Namaqualand and since 1990 has formed the international border between Namibia and South Africa. The contributors to this volume focus on this hardly discussed stretch of the Orange River to understand the region's social history, geography, and economy. This book brings together scholars from Namibia, South Africa, and overseas, as well as the knowledge and analysis from people living in the region. In concise chapters and short portraits, they discuss the region's past and present from a variety of perspectives.